Prognostic Implications of Guideline-Directed Medical Therapy for Heart Failure in Functional Mitral Regurgitation: A Systematic Review and Meta-Analysis - Vasileios Anastasiou; Andreas S. Papazoglou; Stylianos Daios; Dimitrios V. Moysidis; Eirinaios Tsiartas; Matthaios Didagelos; Kyriakos Dimitriadis; Theodoros Karamitsos; George Giannakoulas; Konstantinos Tsioufis; Antonios Ziakas; Vasileios Kamperidis (Diagnostics)
Objectives: Randomized evidence on the role of heart failure guideline-directed medical therapy for patients with functional mitral regurgitation (FMR) is lacking. The present meta-analysis sought to investigate the prognostic impact of different pharmacotherapy categories recommended in heart failure on subjects with FMR. Methods: A systematic literature review was conducted to identify studies reporting the association of renin angiotensin system inhibitors (RASi), beta-blockers (BB), and mineralocorticoid receptor antagonists (MRA) with outcomes in FMR. A random-effects meta-analysis was conducted to quantify the unadjusted and adjusted hazard ratios [(a)HRs] for all-cause death and the composite outcome in each medical category. Results: Twelve studies with 6,715 FMR patients were included. The use of RASi and BB was associated with a significantly lower risk of all-cause mortality (HR 0.52 [0.39–0.68]; p < 0.00001, I2 = 62% and HR 0.62 [0.49–0.77]; p < 0.0001, I2 = 44%, respectively) and the composite outcome (HR 0.54 [0.44–0.67]; p < 0.00001, I2 = 33% and HR 0.62 [0.52–0.75], p < 0.00001, I2 = 35%, respectively) in unadjusted models. Both RASi (aHR 0.73 [0.56–0.95], p = 0.02, I2 = 52%) and BB (aHR 0.60 [0.41–0.88], p = 0.009, I2 = 55%) retained their association with the composite outcome in pooled adjusted models. The prognostic benefit of using RASi or BB was retained in subgroup analyses including only (1) patients with moderate or severe FMR and (2) patients with reduced or mildly reduced left ventricular ejection fraction. MRA did not demonstrate a significant association with improved outcomes. Conclusions: RASi and BB administration appear to have a favorable prognostic impact on patients with FMR, regardless of the severity of regurgitation.